2015
DOI: 10.1186/s12889-015-2480-0
|View full text |Cite
|
Sign up to set email alerts
|

A survey on HIV-related health-seeking behaviors among transgender individuals in Jakarta, based on the theory of planned behavior

Abstract: BackgroundMale-to-female transgender (waria) individuals are at high risk for HIV. This study aims at mapping the psychological determinants of four HIV-related health-seeking behaviors. This knowledge can be used to develop effective interventions to prevent the spread of HIV/AIDS.MethodsThe study involved 209 waria from five districts in Jakarta, selected with a cluster sampling procedure. Cross-sectional data were gathered through structured interviews. The four examined behaviors are, visiting sexually tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…HIV prevalence among transgender women Transgender individuals are those whose gender identities and/or gender expression do not fully align with their assigned sex at birth. Many cultures around the world recognize transgender people using varied terms such as ''Kathoeys'' in Thailand [1]; ''Hijras'' in India, Bangladesh and Pakistan [2Á4]; ''Warias'' in Indonesia [5]; the ''Rae Rae's'' and ''Mahu's'' in French Polynesia [6]; and ''Travestis'' of Latin America [7]. Currently, there are no national-level estimates of the prevalence of transgender identity for any country, although India, Bangladesh, Nepal and Pakistan have recently added a third gender option to the census.…”
Section: Introductionmentioning
confidence: 99%
“…HIV prevalence among transgender women Transgender individuals are those whose gender identities and/or gender expression do not fully align with their assigned sex at birth. Many cultures around the world recognize transgender people using varied terms such as ''Kathoeys'' in Thailand [1]; ''Hijras'' in India, Bangladesh and Pakistan [2Á4]; ''Warias'' in Indonesia [5]; the ''Rae Rae's'' and ''Mahu's'' in French Polynesia [6]; and ''Travestis'' of Latin America [7]. Currently, there are no national-level estimates of the prevalence of transgender identity for any country, although India, Bangladesh, Nepal and Pakistan have recently added a third gender option to the census.…”
Section: Introductionmentioning
confidence: 99%
“…The ARV administration to HIV/AIDS patients could significantly reduce oral candidiasis. Some patients in this study previously had ARV therapy, while the new HIV/AIDS patients had not received the therapy yet 21, 22 . Fungal infection was still found in most patients with antifungal therapy history, both systemic and topical 23 .…”
Section: Discussionmentioning
confidence: 97%
“…Basar et al (29) stated that high perceived discrimination, poor social support, and poor family support can affect self-esteem and gender dysphoria mental health by degrading the quality of life. Prabawanti et al (17) stated that MtF gender dysphoric individuals are often stigmatized and discriminated, forcing them to become sex workers because it is difficult to compete for employment in Jakarta, when only having a high school education. Although discriminatory acts are legally prohibited, MtF gender dysphoric individuals experience discrimination that causes difficulties in completing education, job search, housing ownership and access to general health services.…”
Section: Discussionmentioning
confidence: 99%
“…They have a low economic status (earning less than Rp 3.100.000 /month) and most live in villages, occupying a narrow boarding-house room. Research by Prabawanti et al (17) in MtF gender dysphoric individuals in DKI Jakarta showed that 42% had junior high school education, 60% were commercial sex workers (34.9% as sex worker Table 3. Factors associated with quality of life in MtF gender dysphoric individuals (n=106) Note: CI= 95% confidence interval for the mean; p*= significant association; @ Adjusted odds ratio controlled for variables for their main income and 24.4% for additional income).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation